From Banff 1991 to Today: The Changing Landscape of the v-Lesion in Kidney Transplant Rejection - Karolien Wellekens; Karolien Wellekens; Priyanka Koshy; Priyanka Koshy; Candice Roufosse; Maarten Naesens; Maarten Naesens (Transplant International)
Intimal arteritis (v-lesion) has long been considered a hallmark of higher-grade T cell-mediated rejection (TCMR) in kidney transplantation, historically associated with poor graft survival and resistance to therapy. These associations have informed treatment strategies, often prompting intensified immunosuppression, including anti-thymocyte globulins (ATG). However, emerging evidence challenges the assumption that all v-lesions signify TCMR—particularly when they occur in isolation, without significant tubulo-interstitial inflammation. Recent observational studies and molecular analyses suggest that isolated v-lesions may instead reflect non-immune injury mechanisms, such as ischemia-reperfusion injury, particularly in the early post-transplant period. In addition, the shared nature of the v-lesion between TCMR and antibody-mediated rejection (AMR) raises concerns about overdiagnosis and potential overtreatment of “mixed rejection” phenotypes. Following advances in modern immunosuppression and improved donor-recipient matching, the clinical course of v-lesions may have evolved, with severe v3 presentations now rare—rendering historical comparisons less applicable to current practice. These insights highlight the need to revisit traditional paradigms and adopt a more nuanced, context-aware interpretation of v-lesions. This review integrates historical and contemporary perspectives, advocating for a reappraisal of the role of the v-lesion in kidney transplant biopsy evaluation.